Association between BMP4 rs17563 Polymorphism and NSCL/P Risk: A Meta-Analysis. (12th January 2015) - Hu, Yuan-Yuan; Qin, Chuan-Qi; Deng, Mo-Hong; Niu, Yu-Ming; Long, Xing
Abstract : Objective. To investigate the association between bone morphogenetic protein 4 (BMP4) rs17563 polymorphism and nonsyndromic cleft lip with or without palate (NSCL/P) risk. Methods. Four online databases were researched and the related publications were collected. Odds ratio (OR) with 95% confidence interval (CI) was applied to assess the relationship; publication bias, metaregression, and sensitivity analysis were conducted to guarantee the strength of results. Results. Six published case-control studies were collected. Overall, no significant association between BMP4 rs17563 polymorphism and NSCL/P risk was found. It was notable that significant susceptibility on different ethnicity was observed in the stratified analysis. For Chinese population, the BMP4 rs17563 polymorphism was a significantly increased risk for NSCL/P (C versus T: OR = 1.52, 95% CI = 1.28–1.82, P < 0.01, I 2 = 0 %; CC versus TT: OR = 2.58, 95% CI = 1.74–3.82, P < 0.01, I 2 = 0 %; TC + CC versus TT: OR = 1.45, 95% CI = 1.14–1.84, P < 0.01, I 2 = 0 %; CC versus TT + TC: OR=2.46, 95% CI = 1.46–4.14, P < 0.01, I 2 = 47.0 %). On the contrary, significantly protective effects were found in Brazilian population (C versus T: OR = 0.69, 95% CI = 0.50–0.96, P = 0.03, I 2 = 68.5 %; TC versus TT: OR = 0.52, 95% CI = 0.40–0.68, P < 0.01, I 2 = 0 %; TC + CC versus TT: OR = 0.52, 95% CI = 0.35–0.78, P < 0.010, I 2 = 54.4 %). Conclusion . This meta-analysis indicated that BMP4 rs17563 polymorphism could play a different role during the development of NSCL/P based on ethnicity diversity.